Psychological dimensions in the drawings of children of financially poor families - Khayif, Sukaina Hasan (Linguistics and Culture Review, 2021)
The current research deals with an important category of society, namely, children in the primary education stage (fourth primary), which is an important stage of human development, as the child of different sex witnesses changes from different aspects of sexual, mental and emotional development. After the researcher took and looked at a group of drawings of children of financially poor families who are 9 years old, it became clear to them some characteristics and psychological dimensions that emerged clearly and tangibly, which were developed by children in the form of subconscious projections through shapes, colors and lines, in drawing children of poor families Of the parts of the human body, we clearly notice the psychological dimensions through drawing those parts, as it tends to draw (the size of the human head is large), which indicates that the child suffers from frustration or excessive sensitivity and excessive preoccupation with fantasies, and exaggeration in drawing the size of the head greatly expresses On the individual's need to depend on others.